Microcephaly caused by the Zika virus: dental care - MORO,Juliana da Silva (2019)
ABSTRACT Zika virus infection was declared a public health emergency at national and international levels due to the high incidence of the virus infection and its relationship with the birth of children with microcephaly. Patients with microcephaly present significant clinical neuropsychomotor disorders, therefore, dental surgeons should be prepared to treat such patients, observing the possible alterations associated with this condition, as well as the oral diseases. Thus, the purpose of this research study was to inform dental surgeons about the microcephaly associated with the Zika virus, as well as instructing them about the dental care necessary for such condition and its management during the consultations.